PREGNANCY OUTCOME IN WOMEN PRESENTING WITH OBSTRUCTED LABOUR IN A RURAL HOSPITAL, KENYA - Gichuhi, J Wanyoike; Soita, M; Kiragu, J. M (My University, 2015)
Background: Obstructed labour still remains a life – threatening catastrophe all over the world but mostly in the developing countries. This, entirely preventable labour complication carrying a very high maternal and neonatal morbidity and mortality is an indicator of the inadequacy and poor quality of obstetric care. Obstructed labour is a major cause of maternal and perinatal morbidity and mortality accounting for an estimated 8% of maternal deaths (4). Objective: To determine the pregnancy outcome in mothers presenting with obstructed labour compared to other parturient undergoing emergency caesarean section. Study Design: Prospective cohort study. Study setting: Kakamega Provincial General Hospital, Kenya. Subjects and Methods: The study group comprised of 135 mothers with obstructed labour while the comparison group also comprised of 135 mothers. Data collected was analyzed in SPSS version 15.0. Data analysis entailed the use of descriptive statistics such as frequency distributions and cross tabulations using the chi-square statistics Results: The prevalence of obstructed labour was 6.8%. Women with obstructed labour had low educational and socioeconomic status compared to the comparison group (p 0.032, 0.05). While 90% of mother with obstructed labour had attended antenatal clinic only 49% had intended to deliver in hospital. Factors that contributed to the delay in presenting to hospital included; lack of funds (27%), husband or mother in-law refusal to give consent for hospital delivery (26%), lack of transport or ambulance at the primary and secondary level facility (17%). Obstructed labour was associated with significant maternal morbidities; ruptured uterus 6%, obstetric hysterectomy 5.2% (p 0, 0015), uterine tears 14.8% (p 0.000), post partum haemorrhage 14.9% (p 0.000), wound sepsis 43% (p 0.0001) and puerperal sepsis 26.7% (0.000).Obstructed labour was also associated with significant fetal morbidities; stillborns 18.5% (p 0.0001), low Apgar score 30%, newborn unit admission 26.6% (p 0.0001) and neonatal sepsis 16.5% (p 0.0001). Conclusion: There is need to improve the educational and socio-economic status of the women. Restructuring of Maternal child Health services should be done with particular attention to increasing community awareness on safe obstetric care, promotion and improvement of appropriate technology, counselling skill to health care providers through training, structured and quality health talks to the antenatal clients on safe obstetric care.. Provision of accessible and effective safe obstetric care through partnership with the community is paramount.